PTH-102 Treatment Of Benign Pancreatic Duct Strictures With Fully Covered Self Expandable Metal Stents (fc-sems) Is Feasible, Safe And Effective In Patients With Symptomatic Chronic Pancreatitis (cp). (9th June 2014) - Rameshshanker, R; Kaltsidis, H; Vlavianos, P; Phillips, N; Westaby, D
Abstract : Introduction: FC-SEMS have been used for treatment of benigh biliary strictures (BBS) with excellent results. Pancreatic duct strictures (PDS) of CP vary in length and complexity and associated with upstream dilatation and/or stones. Limited data on aggressive endotherapy (ET) with insertion of the repeated plastic stents (PS) showed good response. Experience with FC-SEMS in pancreatic strictures is limited. Methods: Aim:To assess feasibility and safety of smaller diameter (8 mm) FC-SEMS for treatment of CP with dominant downstream strictures either de novo or as resque (failed previous ET). Methods: All patients referred to our tertiary institution for pancreatic intervention and successfully underwent SEMS were included. Response (i.e. pain control) was assessed at 3 months by using a 1–10 visual analogue scale to compare pre- and post-intervention symptoms (a score <2 is complete, 3 or above is partial response). Results: A total of 15 patients (8 male and 7 female, mean age 52) received FC - SEMS 10 in main PD and 5 in the accessory duct (Santorini). 13 had previous endotherapy while for 2 patients this was the first attempt at endotherapy. 4 individuals with PD stones had ESWL prior to ERCP. Table 1 summarises the data on this patient group. Placement of stents was feasible in all individuals. All had their stents removed at 4 months or earlier if they were symptomatic. One stent migrated proximally and associated with formation of an accessory duct abscess treated with antibiotics and stent removal. At 3 months, a total of 9 patients (60%) reported complete resolution of pain whereas in another 2 (13%) the response was parial. In the remaiing 4 individuals (27%) there was no improvement after placement of FC-SEMS and those were subsequently removed; these individuals are considered for surgical drainage. 3 patients (2 complete responders and 1 partial responder) developed new strictures at the proximal end of the stents. Conclusion: Placement of FC-SEMS for treatment of BPS is feasible with an acceptable safety profile. Stent migration occured in one. New strictures seen in 3 patients and warrant further assessment. Future FC-SEMS designed for use in the pancreas may overcome this problem. Disclosure of Interest: None Declared.